2014
DOI: 10.1073/pnas.1409026111
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of sympathetic endothelin A receptors for adverse cardiac remodeling

Abstract: Significance In failing hearts, norepinephrine (NE) net release and endothelin-1 (ET1) levels are increased. ET1 receptor antagonists were successfully used in preclinical heart failure (HF) studies, but clinical studies did not show beneficial effects in HF patients. We found that mice lacking endothelin receptor A (ET A ) only in sympathetic neurons but not in cardiomyocytes were protected from the development of HF. Mechanistically, the presynaptic reuptake of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…With regard to nerves, myocardial tissue is innervated to regulate heart function. Cardiac pressure overload in adult mice reduced myocardial nerve density, and a similar pattern is observed in human failing myocardium (49)(50)(51). In contrast, in our regenerative pressure overload model, an increased myocardial axonogenesis was detected, which might promote cardiac contractility (e.g., through the release of norepinephrine) and -on the other hand -promote cardiomyocyte proliferation by secreting factors such as neuregulin-1 (52,53).…”
Section: Discussionsupporting
confidence: 69%
“…With regard to nerves, myocardial tissue is innervated to regulate heart function. Cardiac pressure overload in adult mice reduced myocardial nerve density, and a similar pattern is observed in human failing myocardium (49)(50)(51). In contrast, in our regenerative pressure overload model, an increased myocardial axonogenesis was detected, which might promote cardiac contractility (e.g., through the release of norepinephrine) and -on the other hand -promote cardiomyocyte proliferation by secreting factors such as neuregulin-1 (52,53).…”
Section: Discussionsupporting
confidence: 69%
“…1994; Lehmann et al. 2014) and we previously showed that coronary vessels from EC‐MR −/− have attenuated endothelin‐induced vasoconstriction (Mueller et al. 2015).…”
Section: Resultsmentioning
confidence: 91%
“…1994; Lehmann et al. 2014). Thus, an intriguing possibility is that EC‐MR mediates endothelin‐1‐induced vasoconstriction of coronary vessels in TAC mice through its receptors ETA and ETB in the setting of pressure overload, thereby contributing to impaired coronary blood flow and resulting in systolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative possibility is that the ET and adrenergic systems are serially coupled downstream of GPR81 activation (Supplemental Figure 5). In support of this, there is evidence that ET receptor A agonism can enhance adrenergic tone by at least 2 mechanisms: (a) via decreasing the reuptake of norepinephrine by the presynaptic nerve terminals at neuromuscular junctions (41) and (b) by increasing sympathetic tone (42).…”
Section: Discussionmentioning
confidence: 96%